Novel HAX1 Gene Mutation in a Vietnamese Boy with Severe Congenital Neutropenia - Tham Thi Tran; Quang Van Vu; Taizo Wada; Akihiro Yachie; Huong Le Thi Minh; Sang Ngoc Nguyen (Hindawi Limited, 2018)
Severe congenital neutropenia (SCN) is a rare disease that involves a heterogeneous group of hereditary diseases. Mutations in the HAX1 gene can cause an autosomal recessive form of SCN-characterized low blood neutrophil count from birth, increased susceptibility to recurrent and life-threatening infections, and preleukemia predisposition. A 7-year-old boy was admitted due to life-threatening infections, mental retardation, and severe neutropenia. He had early-onset bacterial infections, and his serial complete blood count showed persistent severe neutropenia. One older sister and one older brother of the patient died at the age of 6 months and 5 months, respectively, because of severe infection. Bone marrow analysis revealed a maturation arrest at the promyelocyte/myelocyte stage with few mature neutrophils. In direct DNA sequencing analysis, we found a novel homozygous frameshift mutation (c.423_424insG, p.Gly143fs) in the HAX1 gene, confirming the diagnosis of SCN. The patient was successfully treated with granulocyte colony-stimulating factor (G-CSF) and antibiotics. A child with early-onset recurrent infections and neutropenia should be considered to be affected with SCN. Genetic analysis is useful to confirm diagnosis. Timely diagnosis and suitable treatment with G-CSF and antibiotics are important to prevent further complication.